FSW Welding Parameters Effect on Lap Joint Property of Aluminum Alloy and Stee - กิมะพงศ์ กิตติพงษ์; มีมนต์ อนินท์ (Frontiers in Engineering Innovation Research, 2006)
A lap joint of A5083 aluminum alloy and SS400 steel was produced by Friction Stir Welding (FSW) using the various process parameters such as rotational speed, traverse speed and pin depth . The variations of welding parameters produced various characteristic interfaces and had conspicuous influences on the joint properties. Increasing the rotational speed decreased the shear load of the joint due to producing a thick FeAl[subscript3] intermetallic compound (IMC) at the interface. When traverse speed increased, the shear load increased because IMC thickness at the interface decreased, however. when the speed was so high. An incomplete interface was formed. Increasing the pin depth produced a thick FeAl3 IMC phase and an incomplete interface that directly deteriorated the shear load of the joint.